Hard carbon negative electrode material, preparation method thereof and sodium ion battery
By co-modification of asphalt, oxidation and carbonization, hard carbon negative electrode materials with high reversible capacity and excellent rate performance were prepared, and the poor capacity and rate performance of asphalt-based hard carbon in sodium ion batteries in the prior art was solved. The problem.
Patent Information
- Application Number
- CN202411452200.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The hard carbon negative electrode materials prepared with asphalt as the precursor in existing sodium ion batteries have problems such as low reversible capacity, low voltage platform area capacity and poor rate performance.
Nitrification treatment is performed on asphalt, followed by oxidation heat treatment under an oxygen-containing atmosphere, and then carbonization heat treatment is performed in an inert atmosphere. Through the coordinated modification treatment method of nitration first and then oxidation, nitrogen elements are introduced to promote pore formation and reduce crystallinity. , hard carbon negative electrode material with high reversible capacity and excellent rate performance was prepared.
The high reversible capacity and excellent rate performance of hard carbon negative electrode materials are achieved, effectively solving the capacity and voltage platform problems of bitumen-based hard carbon in sodium ion batteries.
Smart Images

Figure CN119320128A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the non-renewable nature of traditional fossil energy and increasingly severe environmental problems, new energy technologies represented by lithium-ion batteries are increasingly being used in electronic devices, electric vehicles and other fields due to their advantages in environmental renewability, energy and power density. Sodium-ion batteries, which work in a similar way to lithium-ion batteries, are expected to replace lithium batteries in many fields such as large-scale energy storage equipment and small low-speed electric vehicles due to their abundant reserves in the earth's crust, low costs and relatively mature production and preparation processes. In recent years, research progress related to sodium-ion batteries has received close attention from academia and industry.
[0003] Combined with the working principle of sodium ion batteries, hard carbon is considered to be the most promising sodium negative electrode material for industrialization due to its short-range ordered and long-range disordered graphite-like domain structure, abundant closed pores and defects, high reversible capacity and low working potential. The types of hard carbon precursors generally include biomass, organic polymers, asphalt, etc. Among them, biomass raw materials are rich in sources, complex in natural components, and have more defects after carbonization, which are conducive to providing sodium storage sites. However, its early pretreatment process is complex, the source of raw materials is unstable, and it has a low yield and high ash content after carbonization; organic polymers such as resins rely on their stable cross-linked structure. The carbonization process can effectively inhibit the planar orderly rearrangement of the carbon layer, thereby obtaining hard carbon with excellent sodium storage performance. However, this type of material needs to undergo secondary synthesis processing in chemical plants, which is costly; asphalt is a common petrochemical extract with a wide source and low cost. The aliphatic segments, unsaturated aromatic rings, condensed ring structures and heteroatoms in its components can produce more defects during the carbonization process, expand the distance between carbon layers, and facilitate the storage and deintercalation of sodium ions. It is a common precursor of hard carbon materials.
[0004] Compared with biomass and organic polymer precursors, hard carbon prepared with asphalt as a precursor has advantages in cost and yield, but asphalt is prone to orderly rearrangement of carbon layers during high-temperature carbonization, forming a large-area planar stacked graphite-like domain structure. The reduction of amorphous structure and the reduction of carbon layer spacing are not conducive to the stable embedding and deintercalation of sodium ions in the structure. Therefore, the hard carbon negative electrode material prepared with asphalt as a precursor often has a low specific capacity (<260mAh / g), less capacity in the low voltage platform area, and poor rate performance.
[0005] Application Contents
[0006] In view of this, the present application provides a hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery, aiming to obtain a sodium ion battery hard carbon negative electrode with high reversible capacity and excellent rate performance.
[0007] The embodiment of the present application is implemented by providing a method for preparing a hard carbon negative electrode material, comprising: nitrating asphalt with nitric acid to obtain nitrated asphalt; performing oxidative heat treatment on the nitrated asphalt in an oxygen-containing atmosphere to obtain oxidized asphalt; and carbonizing heat treatment on the oxidized asphalt in an inert atmosphere to obtain the hard carbon negative electrode material.
[0008] In some embodiments, the nitration treatment of the asphalt using nitric acid includes: mixing an aqueous nitric acid solution with the asphalt, and performing a mixing reaction under an inert atmosphere.
[0009] In some embodiments, the mass percentage of nitric acid in the nitric acid aqueous solution is 30% to 65%; and / or, the ratio of the mass of the asphalt to the volume of the nitric acid aqueous solution is 1:1 to 1:15; and / or, the nitric acid aqueous solution includes sulfuric acid; and / or, the inert atmosphere includes an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon; and / or, the temperature of the mixed reaction is 0 to 20°C; and / or, the time of the mixed reaction is 12 to 24 hours.
[0010] In some embodiments, after the mixing reaction, the process further comprises: solid-liquid separation and drying to obtain the nitrated asphalt powder, wherein the drying temperature is 80-120°C.
[0011] In some embodiments, the asphalt includes one or more of petroleum asphalt and coal asphalt; and / or the softening point of the asphalt is 100°C to 350°C; and / or the asphalt is asphalt granules or asphalt powder; and / or the average particle size of the asphalt is 10 to 100 μm.
[0012] In some embodiments, the oxygen-containing atmosphere is a pure oxygen atmosphere, an air atmosphere, or a mixed atmosphere formed by oxygen and an inert gas; and / or the holding temperature of the oxidation heat treatment is 150 to 400°C; and / or the holding time of the oxidation heat treatment is 2 to 8 hours; and / or the heating rate of the oxidation heat treatment is 3 to 5°C / min.
[0013] In some embodiments, the inert atmosphere in the carbonization heat treatment includes an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon; and / or the temperature of the carbonization heat treatment is 1100-1700°C; and / or the time of the carbonization heat treatment is 2-8h; and / or the carbonization heat treatment also includes a pre-carbonization treatment before the carbonization heat treatment, and the temperature of the pre-carbonization treatment is 600-900°C.
[0014] Correspondingly, an embodiment of the present application also provides a hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.
[0015] In some embodiments, the median particle size of the hard carbon negative electrode material is 7 to 20 μm.
[0016] Correspondingly, an embodiment of the present application also provides a sodium ion battery, comprising the above-mentioned hard carbon negative electrode material, or comprising the hard carbon negative electrode material prepared by the above-mentioned preparation method.
[0017] The preparation method of the hard carbon negative electrode material of the present application comprises: nitrating asphalt with nitric acid to obtain nitrated asphalt; performing oxidation heat treatment on the nitrated asphalt in an oxygen-containing atmosphere to obtain oxidized asphalt; performing carbonization heat treatment on the oxidized asphalt in an inert atmosphere to obtain the hard carbon negative electrode material. By using the synergistic modification treatment method of nitration followed by oxidation, nitrogen is introduced and oxidized into the asphalt, and pore formation can be promoted, and its crystallinity can be reduced and microporous. The prepared hard carbon negative electrode material has high reversible capacity and excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a hard carbon negative electrode material provided in the present application;
[0020] Figure 2 The charge and discharge curves of Example 1 and Comparative Example 1;
[0021] Figure 3 The charge and discharge curves of Example 1, Comparative Example 2 and Comparative Example 4;
[0022] Figure 4 The charge and discharge curves of Example 2, Comparative Example 3 and Comparative Example 5 are shown;
[0023] Figure 5 It is a ratio diagram of Example 1 and Comparative Example 1;
[0024] Figure 6 It is the ratio diagram of Example 1 and Comparative Example 2;
[0025] Figure 7 It is a ratio diagram of Example 1 and Comparative Example 4. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to".
[0027] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0028] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0029] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0030] The present application provides a method for preparing a hard carbon negative electrode material. Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a hard carbon negative electrode material provided by the present application, which specifically includes the following steps:
[0031] Step S1: using nitric acid to nitrate the asphalt to obtain nitrated asphalt;
[0032] Step S2: performing an oxidative heat treatment on the nitrated asphalt in an oxygen-containing atmosphere to obtain an oxidized asphalt;
[0033] Step S3: performing carbonization heat treatment on the oxidized asphalt in an inert atmosphere to obtain the hard carbon negative electrode material.
[0034] In this embodiment, asphalt is used as a precursor and raw material, nitric acid is selected as an electrophilic reagent, and the nitronium ions produced by the decomposition of nitric acid undergo electrophilic aromatic substitution reaction with the aromatic rings in the asphalt, and air pre-oxidation is combined to further introduce oxygen-containing functional groups, which together prevent the orderly rearrangement of the asphalt molecules during the carbonization process, thereby reducing its crystallinity and causing it to become microporous. This method has the advantages of simple process, strong controllability, and low raw material cost. When the asphalt modified as above is carbonized and used for sodium ion storage, it exhibits high sodium storage capacity, abundant low-voltage platform capacity, and excellent rate performance.
[0035] Furthermore, in this embodiment, the asphalt is treated by a synergistic modification method of first nitrification with nitric acid and then pre-oxidation. Before the asphalt raw material is subjected to oxidation treatment such as air oxidation, there are fewer oxygen-containing functional groups and more aromatic hydrogen on its surface. During the nitration process, the active hydrogen at some sites is protonated and released as nitronium ions, which promotes electrophilic aromatic substitution reaction with asphalt, so that a large number of nitrogen-containing functional groups can be introduced into the asphalt molecules. When the oxidation treatment is carried out in an oxygen-containing atmosphere, these nitrogen-containing functional groups will react with oxygen to generate small molecules such as N2O, NO2, N2O4, and N2O5, thereby realizing gas-phase pore formation and increasing the formation of micropores and defects in the asphalt during carbonization; the other part of the nitrogen-containing functional groups is doped into the bulk structure of the asphalt as a nitrogen source, thereby reducing the orderly rearrangement of the asphalt during the carbonization process, expanding the distance between carbon layers, and increasing the disorder. The destination of the two parts of nitrogen together plays a role in regulating the asphalt-based hard carbon structure, preventing the orderly rearrangement of the asphalt molecules during the carbonization process, and promoting its crystallinity reduction and microporous formation.
[0036] The step S1:
[0037] The asphalt may include one or more of petroleum asphalt and coal asphalt. In one embodiment, the softening point of the asphalt may be 100°C to 350°C, and the specific softening point may be 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, etc. Asphalt itself is a complex mixture composed of hydrocarbons of different molecular weights and their non-metallic derivatives. Asphalts with different softening points have different degrees of aromatization. Asphalts with lower softening points correspond to fewer aromatic nuclei and more aliphatic chain segments, which will produce gases during the thermal decomposition process. These gases will distort the carbon lattice and produce a large number of inherent defects and active sites; asphalts with higher softening points correspond to more substantial aromatic nuclei with fewer short aliphatic chains. Due to its higher condensation degree and fewer active sites during the thermal decomposition process, they often participate in the finalization of the carbon layer skeleton. The use of asphalt with a relatively low softening point in this application is conducive to the formation of hard carbon.
[0038] Furthermore, the asphalt may be in the form of asphalt particles or asphalt powder, so that the asphalt can be more fully contacted with nitric acid, increasing the contact area between nitric acid and asphalt, and more fully undergoing nitration treatment. Specifically, the average particle size of the asphalt may be 10 to 100 μm.
[0039] In one embodiment, the nitration treatment of the asphalt using nitric acid specifically includes: providing a mixed solution containing nitric acid and asphalt, and performing a mixing reaction under an inert atmosphere.
[0040] In a specific embodiment, before providing the mixed solution containing nitric acid and asphalt, the method further includes: mixing the nitric acid aqueous solution with the asphalt.
[0041] The mass fraction of the nitric acid aqueous solution is 30% to 65%, that is, the mass percentage of nitric acid in the nitric acid aqueous solution is 30% to 65%, specifically 30%, 40%, 50%, 60%, 65% and the like.
[0042] Specifically, the mass-to-volume ratio of asphalt and nitric acid aqueous solution can be 1:1-1:15, that is, the ratio of the mass of asphalt to the volume of nitric acid aqueous solution is 1:1-1:15, specifically 1:1-1:2, 1:2-1:3, 1:3-1:4, etc.
[0043] In one embodiment, sulfuric acid is also added to the nitric acid aqueous solution, and the use of sulfuric acid can promote the protonation of nitric acid and accelerate the reaction rate of the nitration reaction. At the same time, sulfuric acid can also be used as a dehydrating agent to remove water in time to accelerate the reaction.
[0044] In a specific embodiment, the nitric acid aqueous solution can be prepared by mixing concentrated nitric acid and concentrated sulfuric acid. Specifically, the mass ratio of concentrated nitric acid to concentrated sulfuric acid can be 3:1 to 5:1, specifically 3:1, 4:1, 5:1, etc.
[0045] In this step, the nitrification process is essentially the decomposition of concentrated nitric acid into electrophilic NO 2+ Attack the aromatic ring and then deprotonate. The reaction environment requires that the nitric acid must have a high concentration, that is, the mass fraction of the nitric acid aqueous solution is 30% to 65%; when the concentration of the nitric acid aqueous solution is low, it will induce more oxidation of the highly reactive aliphatic side chains of the asphalt to generate carbonyl or carboxyl groups. After comprehensive consideration, a 65% mass fraction nitric acid aqueous solution is selected as the preferred solution.
[0046] It is understood that the inert atmosphere may include an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon. In a specific embodiment, ventilation may be used to achieve a flowing atmosphere of the inert atmosphere, such as introducing an inert gas at a gas flow rate of 12 to 20 ml / min.
[0047] In one embodiment, during the nitration treatment, the temperature of the mixed reaction can be 0-20°C, specifically 0°C, 5°C, 10°C, 15°C, 20°C, etc. In one specific embodiment, the temperature can be controlled by a water bath, such as an ice water bath. The time of the mixed reaction can be 12-24h, specifically 12h, 18h, 24h, etc.
[0048] It can be understood that the mixing reaction can be carried out by using any mixing method known in the art, such as stirring, ultrasound, and the like.
[0049] Furthermore, after the mixing reaction is completed, solid-liquid separation and drying are performed to obtain nitrated asphalt powder. Furthermore, after solid-liquid separation, deionized water can be used for washing to adjust the pH value to neutral. Specifically, the drying temperature can be 80 to 120°C, such as 80°C, 100°C, 120°C, etc.; the drying time can be 8 to 20 hours, such as 8 hours, 12 hours, 15 hours, 20 hours, etc.
[0050] In one embodiment, before step S1, a step of asphalt doping may be further included, wherein the doping element may be N, P, B, etc. The N element may be mixed with asphalt by nitrogen-containing compounds such as urea.
[0051] In step S2:
[0052] The oxygen-containing atmosphere may be a pure oxygen atmosphere, an air atmosphere, or a mixed atmosphere of oxygen and an inert gas. In a specific embodiment, the oxygen-containing atmosphere may be an air atmosphere.
[0053] The holding temperature of the oxidative heat treatment can be 150-400°C, specifically 150-200°C, 200-250°C, 250-300°C, 300-350°C, 350-400°C, etc. The holding time of the oxidative heat treatment can be 2-8h, specifically 2-4h, 4-6h, 6-8h, etc. In a specific embodiment, the heating rate to the holding temperature can be 3-5°C / min. The holding temperature of the oxidative heat treatment is higher than the softening point of the asphalt, so that the nitroasphalt is melted and oxidized, and oxygen-containing functional groups such as carboxyl and carbonyl are introduced into the molecular structure of the asphalt to induce it to form a cross-linked structure; at the same time, some nitro groups react with oxygen to generate small molecular nitrogen oxides and are discharged, forming defect sites in the asphalt molecules.
[0054] In one embodiment, after the heat preservation is completed, the oxidation heat treatment is cooled to room temperature and crushed or pulverized to obtain oxidized asphalt powder, and then the subsequent steps are carried out.
[0055] In step S3:
[0056] The inert atmosphere may include an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon.
[0057] The temperature of the carbonization heat treatment can be 1100-1700°C, specifically 1100-1200°C, 1200-1300°C, 1300-1500°C, 1500-1700°C, etc.; the time can be 2-8h, specifically 2-4h, 4-6h, 6-8h, etc.
[0058] In one embodiment, the carbonization heat treatment may include a pre-carbonization treatment, and the temperature of the pre-carbonization treatment may be 600-900° C., specifically 600-700° C., 700-800° C., 800-900° C., 650-750° C., 750-850° C., etc. The temperature of the carbonization treatment may be 1-5 hours, specifically 1-2 hours, 2-4 hours, 4-5 hours, etc.
[0059] In a specific embodiment, the pre-carbonization treatment and the carbonization heat treatment can be achieved by continuous heating, that is, first heating to the pre-carbonization temperature and then keeping it warm for a corresponding time, then continuing to heat to the pre-carbonization holding time, and then keeping it warm for a corresponding time.
[0060] In another specific embodiment, the material is cooled to room temperature after the pre-carbonization treatment, and then the carbonization heat treatment is performed. Furthermore, before the carbonization heat treatment, a crushing or pulverizing step may be performed to break the material into particles or powders, or to crush or pulverize the material into smaller particles or powders.
[0061] In one embodiment, after step S3, a coating process is further included, and the coating material can be one or more of coating asphalt, tar, etc.
[0062] The present application provides a hard carbon negative electrode material, which is obtained by the preparation method provided by the present application. In one embodiment, the median particle size of the hard carbon negative electrode material is 7-20 μm, specifically 7-10 μm, 10-25 μm, 15-20 μm, etc.
[0063] The present invention also provides an application of a nitrated asphalt hard carbon negative electrode material, which is applied as a negative electrode material for a sodium ion battery.
[0064] The sodium ion battery assembled with the nitrated pitch hard carbon as the negative electrode material of the present application has excellent electrochemical performance, which effectively solves the problem of low reversible capacity of the current pitch-based hard carbon and the low capacity of the low voltage platform caused by the formation of soft carbon after carbonization. And the hard carbon negative electrode material still has good electrochemical performance at high rates.
[0065] The technical scheme and technical effects of the present application are described in detail below through specific embodiments, comparative examples and experimental examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application. Unless otherwise specified, the raw materials, reagents, equipment, etc. used in the following examples can be purchased through conventional commercial channels or prepared under conventional conditions in accordance with regulations.
[0066] Example 1
[0067] This embodiment provides a method for preparing a hard carbon negative electrode material using nitrated pitch, comprising the following steps:
[0068] S1. Slowly add concentrated nitric acid with a mass fraction of 65% into a three-necked flask containing 30g of asphalt powder along a glass rod, and introduce high-purity argon gas into the flask, control the gas flow rate in the range of 12-20ml / min, and maintain this state for 10 minutes to ensure that the air in the flask is completely discharged, start the stirring device, and place it in a water bath filled with ice water, so that the mixed material is completely immersed under the water level, control the reaction temperature in the range of 0-5℃, and stir for 12h; wherein the asphalt powder is a petroleum fractionated asphalt with a softening point of 200℃ and an ash content of <0.1%;
[0069] During the entire reaction process, it was observed that the powdered asphalt in the flask dissolved and yellow smoke overflowed, proving that nitric acid and asphalt underwent nitration reaction to generate nitrogen oxides.
[0070] S2. Cool the molten mixture in step S1 and perform solid-liquid separation using a suction filtration device. During the process, the material is continuously rinsed with deionized water. After adjusting the pH value to neutral, the nitrated asphalt is placed in a vacuum oven for drying at 100° C. for 12 hours.
[0071] S3. The dried nitrated pitch in step S2 is taken out and crushed, and placed in a muffle furnace in an air atmosphere for heating treatment. The heating rate of this step is set to 3-5°C / min, the heating temperature is set to 250°C, and the insulation time is set to 4h to obtain the nitrated pitch after pre-oxidation treatment.
[0072] S4, cooling and crushing the pre-oxidized nitroasphalt described in step S3 to obtain pre-oxidized and modified pre-carbonized powder.
[0073] S5. Place the pre-oxidation oxide powder described in step S4 into a tubular furnace with a high-purity argon atmosphere for high-temperature carbonization. The heating rate of this step is set to 3°C / min, the gas flow rate in the tubular furnace is set to 20 ml / min, the heating temperature is set to 1300°C, and the insulation time is set to 2h to obtain an asphalt-based hard carbon negative electrode material after high-temperature carbonization treatment; the high-temperature carbonization treatment causes the nitrated asphalt carbon layer to rearrange, the saturated carbon and hydrogen components to dehydrogenate and condense, and some nitrogen and oxygen functional groups to escape in the form of gaseous small molecules, and form a large number of pore defects, which are beneficial to the deintercalation of sodium ions.
[0074] S6. The asphalt-based hard carbon negative electrode material prepared in this embodiment is prepared as a negative electrode plate. According to the mass ratio of 8:1:1, 80 mg of asphalt-based hard carbon material, 10 mg of conductive carbon black (superp), and 500 ul of sodium alginate solution with a concentration of 20 mg / ml are weighed, and the mixture is evenly mixed and stirred for 10 minutes to form a black slurry. The slurry is evenly coated on the carbon-coated aluminum foil with a 200 μm scraper. The slurry is first placed in an 80°C blast oven and dried for 1 hour to remove the water in the sodium alginate binder. The slurry is then placed in a vacuum oven at 105°C and dried for 6 hours. The dried plate is taken out, and the carbon-coated aluminum foil with active materials is cut into disc-shaped negative electrode plates with a slicer, and randomly transferred to the glove box for standby use.
[0075] S7. Assemble the asphalt-based hard carbon negative electrode material prepared in this embodiment into a sodium ion battery. The battery is assembled in a glove box filled with Ar atmosphere, using the asphalt-based hard carbon electrode described in step S6 as the electrode, the sodium sheet as the counter electrode, and commercial 1.0M NaPF6 in DIGLYME=100Vol% as the electrolyte to assemble into a button cell.
[0076] Embodiment 2:
[0077] Compared with Example 1, the difference is that asphalt powder with a softening point of 250° C. is used in step S1.
[0078] Embodiment 3:
[0079] Compared with Example 1, the difference is that: in step S1, asphalt powder with a softening point of 250° C. is used, and the mass fraction of nitric acid used is adjusted to 30%.
[0080] Comparative Example 1:
[0081] Compared with Example 1, the difference is that 65wt% of nitric acid in step S1 is replaced by hydrogen peroxide.
[0082] Comparative Example 2:
[0083] Compared with Example 1, the difference is that steps S1 and S2 are omitted, and the pure asphalt powder with a softening point of 200° C. without nitration is directly placed in a muffle furnace for pre-oxidation, and then placed in a tubular furnace for high-temperature carbonization.
[0084] Comparative Example 3:
[0085] Compared with Example 1, the difference is that steps S1 and S2 are omitted, and the pure asphalt powder with a softening point of 250°C without nitration is directly placed in a muffle furnace for pre-oxidation, and then placed in a tubular furnace for high-temperature carbonization.
[0086] Comparative Example 4:
[0087] Compared with Example 1, the difference is that steps S3 and S4 are omitted, and the nitrated powder with a softening point of 200° C. after nitration treatment is directly put into a tubular furnace for high-temperature carbonization.
[0088] Comparative Example 5:
[0089] Compared with Example 1, the difference is that steps S3 and S4 are omitted, and the nitrated powder with a softening point of 250° C. after nitration treatment is directly put into a tubular furnace for high-temperature carbonization.
[0090] The charge and discharge performance of the button cells of the above-mentioned embodiments and comparative examples were tested. The battery testing method adopted constant current charge and discharge. The charge and discharge tests were carried out at a current density of 0.1C, with a discharge cut-off voltage of 0V, a charge cut-off voltage of 2.5V, and a nominal specific capacity of 200mAh / g.
[0091] The rate performance of the button batteries of the above embodiments and comparative examples was tested. The battery test adopted the Xinwei battery testing system, and the test method adopted constant current charge and discharge. The charge and discharge tests were carried out at current densities of 0.1C, 0.5C, 1C, 2.5C, 5C, 10C, 20C, and 0.1C respectively. The discharge cut-off voltage was 0V, and the charge cut-off voltage was 2.5V.
[0092] The test results are shown in Table 1 and Figure 2-Figure 7 .in, Figure 2 The charge and discharge curves of Example 1 and Comparative Example 1 are shown in FIG. Figure 3The charge and discharge curves of Example 1, Comparative Example 2 and Comparative Example 4 are as follows: Figure 4 2 are the charge and discharge curves of Example 2, Comparative Example 3 and Comparative Example 5, Figure 5 is a ratio diagram of Example 1 and Comparative Example 1, Figure 6 is a ratio diagram of Example 1 and Comparative Example 2, Figure 7 It is a ratio diagram of Example 1 and Comparative Example 4.
[0093] Table 1
[0094]
[0095] It can be seen from the charge and discharge curves and rate diagrams of Example 1 that the first-cycle discharge specific capacity of the sodium ion battery assembled with the hard carbon negative electrode material prepared in this example is 365.19 mAh / g, the first-cycle charge specific capacity is 294.07 mAh / g, the charge specific capacity below 0.1 V is 176 mAh / g, and the charge specific capacity at current densities of 10C (2 A / g) and 20C (4 A / g) are 231.46 mAh / g and 160.12 mAh / g, respectively, showing excellent capacity and rate performance.
[0096] From Table 1 and Figure 2-Figure 7 It can be seen that:
[0097] Example 1 and Example 2 have the best reversible capacity and rate performance. This is because they are treated with concentrated nitric acid before pre-oxidation, and the degree of nitration reaction is the highest, and they have excellent ionic conductivity under the corresponding large current density; while Example 3 only reduces the nitric acid concentration compared with Example 2, indicating that the nitration reaction between asphalt powder and nitric acid requires a higher concentration of nitric acid, and the ability of low-concentration nitric acid to decompose into NO2+ and undergo electrophilic aromatic substitution with asphalt is reduced. At this time, dilute nitric acid only plays a role in promoting asphalt oxidation. Note that Example 3 and Comparative Example 3 have similar electrochemical properties, which also indicates that low-concentration nitric acid does not have a good nitration modification on the raw material.
[0098] Compared with Example 1, Comparative Example 1 replaces nitric acid with hydrogen peroxide, and its electrochemical performance is poor, and is at the same level as the unnitrated asphalt in Comparative Example 2. This shows that the role of nitric acid in the modification of asphalt before pre-oxidation is not only as a strong oxidant to promote asphalt oxidation, but also as an electrophilic reagent to undergo electrophilic substitution with asphalt to introduce nitro functional groups.
[0099] Comparative Examples 2 and 3 are unnitrated asphalts. After pre-oxidation and carbonization processes, the high softening point asphalt (i.e., Comparative Example 3) has better reversible capacity and rate performance. This is because the high softening point asphalt itself contains fewer small molecular components such as saturated alkanes and more aromatic components. It can react better with oxygen at the same temperature, and there are more oxygen-containing functional groups in the macromolecules. The later carbonization process forms hard carbon with a high degree of disorder and more defects.
[0100] Comparative Examples 4 and 5 are asphalts with different softening points after nitration, which are directly carbonized without pre-oxidation. Compared with Examples 1 and 2, the synergistic process of nitration followed by pre-oxidation has better electrochemical performance than single nitration treatment.
[0101] The hard carbon negative electrode material and its preparation method and sodium ion battery provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: include: Using nitric acid to nitrate asphalt to obtain nitrated asphalt; performing an oxidative heat treatment on the nitrated asphalt in an oxygen-containing atmosphere to obtain an oxidized asphalt; The oxidized asphalt is subjected to carbonization heat treatment in an inert atmosphere to obtain the hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The nitration treatment of asphalt using nitric acid includes: mixing an aqueous nitric acid solution with the asphalt, and performing a mixing reaction under an inert atmosphere.
3. The preparation method according to claim 2, characterized in that: The mass percentage of nitric acid in the nitric acid aqueous solution is 30% to 65%; and / or, The ratio of the mass of the asphalt to the volume of the nitric acid aqueous solution is 1:1 to 1:15; and / or, The nitric acid aqueous solution includes sulfuric acid; and / or, The inert atmosphere includes an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon; and / or, The temperature of the mixed reaction is 0 to 20° C.; and / or, The mixing reaction time is 12 to 24 hours.
4. The preparation method according to claim 2, characterized in that: After the mixing reaction, the process further comprises: solid-liquid separation and drying to obtain the nitrated asphalt powder, wherein the drying temperature is 80-120°C.
5. The preparation method according to claim 1, characterized in that: The asphalt includes one or more of petroleum asphalt and coal asphalt; and / or, The softening point of the asphalt is 100°C to 350°C; and / or, The asphalt is asphalt granules or asphalt powder; and / or, The average particle size of the asphalt is 10 to 100 μm.
6. The preparation method according to claim 1, characterized in that: The oxygen-containing atmosphere is a pure oxygen atmosphere, an air atmosphere, or a mixed atmosphere formed by oxygen and an inert gas; and / or, The heat preservation temperature of the oxidation heat treatment is 150-400° C.; and / or, The heat preservation time of the oxidation heat treatment is 2 to 8 hours; and / or, The heating rate of the oxidation heat treatment is 3-5°C / min.
7. The preparation method according to claim 1, characterized in that: The inert atmosphere in the carbonization heat treatment includes an atmosphere formed by one or more of nitrogen, helium, neon, argon, and xenon; and / or, The temperature of the carbonization heat treatment is 1100-1700°C; and / or, The carbonization heat treatment time is 2 to 8 hours; and / or, The carbonization heat treatment also includes a pre-carbonization treatment, and the temperature of the pre-carbonization treatment is 600-900°C.
8. A hard carbon negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The hard carbon negative electrode material according to claim 8, characterized in that: The median particle size of the hard carbon negative electrode material is 7 to 20 μm.
10. A sodium ion battery, characterized in that: Comprising the hard carbon negative electrode material according to claim 8 or 9.
Citation Information
Patent Citations
Pitch-based carbon fiber preparation method
CN107904698A
Petroleum asphalt-based carbon fiber flexible electrode material and preparation method and application thereof
CN113871618A
Preparation method and application of oxidation-modified amorphous carbon material
CN114373925A
Asphalt-based hard carbon negative electrode material, preparation method and sodium ion battery
CN115611264A
Hard carbon material and preparation method and application thereof
CN115959647A